Peranan Anggota Kelompok Petani Pengelola Dan Pelestari Hutan Dalam Kegiatan Unit Percontohan Pemanfaatan Hutan Secara Lestari (UP2HL) Di Desa Sukadadi Kecamatan Gedong Tataan - Ktut Murniati (Politeknik Negeri Lampung, 2008)
Forest preservation and rehabilitation in form of model units of sustainable forest culture is intended to improve forest preservation as well as the welfare of the society living around the forest site. In rehabilitation process, the society living around the area or the members of farmers group were the main actors in culturing the forest. The success in managing the efforts of preservation and rehabilitation indeed depended on the role of farmer group available around the forest area. The research was conducted to (1) find out the role of members of farmers group of Wana Asri Forest Preservation in UP2HL program, (2) find out some factors related to the role of the members of farmer group of Wana Asri Forest Preservation in UP2HL program. The research was conducted in Sukadadi Village of Gedong Tataan Sub district of Pesawaran Regency which was selected in purpose. The samples, 84 people, were taken in random with certain proportion. The method used was survey method. The result of the research indicated that the role of the members of the farmer group in rehabilitating the forest is classified medium with score 7,39. The result of hypothesis test showed that there was a significant relationship between the attitude of the farmers towards the UP2HL program and the members of farmers group. However, there was no significant relationship between other free variables and the role of the farmer group members in UP2HL program. Keywords: role, forest preservation, forest rehabilitation